Cortisol dynamics and endothelin-1/nitric oxide ratio are associated with clinical vasospasme (Faculty of Medicine Universitas Indonesia, 2013)
Background: Cortisol dynamics in serum might be related to clinical vasospasm, also known as delayed ischemic neurological deficits (DIND). Two vasoactive substances that play a role in pathophysiology of DIND are endothelin-1 (ET1) and nitric oxide (NO), both are proved associated with cortisol. This study aimed to know how cortisol play a role on ET1/NO ratio and its relationship to DIND. Methods: This was a prospective cohort study for the first 14 days after aneurysmal subarachnoid hemorrhage (SAH). Patients with inclusion criteria will be enrolled for blood test before surgery, and post-operative day 2, 4, 7, and 10 (between 8:00-9:00 AM). The blood tests were performed for cortisol, ACTH, CBG, NO, and ET1. Free cortisol is calculated with Coolens equation. Logistic regression was used to see the interaction model and its scale. Bivariate analysis (corelation) was used to see the relationship between total cortisol, free cortisol, NO, ET1, and clinical vasospasm (DIND). Results: Forty-four patients are enrolled into this study (20 male; 24 females). Mean age is 52.02 years (52.02 ± 11.23). There were 29 patients (66%) within DIND group and 15 patients Non-DIND as the control group. The mean of cortisol level shown is significantly higher in DIND group (35.99 ± 14.24) µg/dL compared to Non-DIND group (19.57 ± 6.19) µg/dL, p < 0.001. The mean of free cortisol level was significantly higher in DIND group (2.06 ± 1.094) µg/dL compared to non-DIND group (0.838 ± 0.365 µg/dL; p < 0.001). The Scatter Plot graph show that correlation of cortisol with ET1/NO ratio started increasing on day 4 and became stronger on day 10. Conclusion: Cortisol is associated with DIND following aneurysmal SAH, probably through its role in keeping the balance between ET1 and NO level. (Med J Indones. 2013;22:161-6. doi: 10.13181/mji.v22i3.585)